Genome sequence of citrobacter sp. Strain a1, a dye-degrading bacterium - Chan, Giek Far (2012)
Citrobacter sp. strain A1, isolated from a sewage oxidation pond, is a facultative aerobe and mesophilic dye-degrading bacterium. This organism degrades azo dyes efficiently via azo reduction and desulfonation, followed by the successive biotransformation of dye intermediates under an aerobic environment. Here we report the draft genome sequence of Citrobacter sp. A1.